2019
DOI: 10.1097/ana.0000000000000553
|View full text |Cite
|
Sign up to set email alerts
|

Portable Infrared Pupillometer in Patients With Subarachnoid Hemorrhage: Prognostic Value and Circadian Rhythm of the Neurological Pupil Index (NPi)

Abstract: Background: Portable automated infrared pupillometry is becoming increasingly popular. To generate an objective reference base, the Neurological Pupil index (NPi) which combines different values of the pupillary light reflex is being introduced into clinical practice. In this explorative study, we examined different aspects of the NPi in relation to clinical severity and outcome in patients with aneurysmal subarachnoid hemorrhage (aSAH). Materials and Methods: Patients with serial assessment of the NPi (NeurOp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Several studies have noted that pupillometer assessment information can provide valuable clinical information about increased intracranial pressure and depth of analgesia and sedation. 9,15,16 Further, pupillometer data can be used as a prognostic indicator and as a noninvasive monitor of the response to osmotic therapy. 9,15,17,18 Neurocritical care units should consider sharing this information on the clinical relevance of pupillometer data in making treatment decisions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have noted that pupillometer assessment information can provide valuable clinical information about increased intracranial pressure and depth of analgesia and sedation. 9,15,16 Further, pupillometer data can be used as a prognostic indicator and as a noninvasive monitor of the response to osmotic therapy. 9,15,17,18 Neurocritical care units should consider sharing this information on the clinical relevance of pupillometer data in making treatment decisions.…”
Section: Discussionmentioning
confidence: 99%
“…9,15,16 Further, pupillometer data can be used as a prognostic indicator and as a noninvasive monitor of the response to osmotic therapy. 9,15,17,18 Neurocritical care units should consider sharing this information on the clinical relevance of pupillometer data in making treatment decisions. Further, it may be helpful for providers to request and integrate pupillometer findings during rounds so neurocritical care nurses can understand the significance of pupillometer metrics.…”
Section: Discussionmentioning
confidence: 99%
“…An NPi score below 3.0 is generally considered an abnormal finding of sluggish light reflex [ 8 ]. Preliminary studies conducted in intensive care units reported the usefulness of QP for detecting a wide range of conditions including increased intracranial pressure [ 7 10 ], response to osmotherapy [ 27 ], discrimination between compressive lesions and microvascular ischemic oculomotor nerve palsy [ 28 ], assessment of disease severity of aneurysmal subarachnoid hemorrhage [ 29 ], the depth of sedation and analgesia [ 30 ], and neurological prognostication in traumatic brain injury and comatose resuscitation-of-spontaneous-circulation following cardiac arrest [ 11 17 , 31 ]. The prognostic implication of QP has been investigated in patients with cardiac arrest [ 11 17 ], in whom a decrease in NPi values less than 2.0 was associated with unfavorable neurological outcomes [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neurologic deterioration is associated with a sudden drop in the NPi value below 2.8, regardless of the side of the lesion ( 37 ). In addition, the NPi might be a useful parameter for estimating the severity of aneurysmal subarachnoid hemorrhage, in which reduced NPi values are associated with poor clinical outcomes ( 38 ). Recently, a single-center study showed that an abnormal NPi <3 from 24 to 72 h following VA ECMO insertion had 100% specificity and 53% sensitivity in predicting 90-day mortality ( 39 ).…”
Section: Clinical Strategiesmentioning
confidence: 99%